2015
DOI: 10.1177/0972150914553526
|View full text |Cite
|
Sign up to set email alerts
|

Are They Really Different? A Study on Apparel Shoppers’ Retail Format Perception in USA and India

Abstract: The retailer's operating environment today is far more complex and interconnected than that which prevailed during the closing of the last century. Given the trends of changing consumer preferences and the growing importance of the emerging destinations for retail expansion, the focus is definitely on the untapped markets owing to their relatively high market growth potential. Whether global or local, the retailer's adaptation to market conditions is crucial. However, heterogeneity of the business landscape an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In most cases the social influence, especially from family, friends, children or even social communities, drives the purchasing intention (Basu, 2015; Conci et al, 2009; Dhar, 2017; East et al, 2014) by generating awareness in the first place, reinforced by subsequent positive word of mouth (Lian & Yen, 2014; Roy et al, 2017). For instance, influence of peers and superiors can have huge impact on the adoption of social networking in the modern societies (Peng & Mu, 2011; Venkatesh & Brown, 2001).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In most cases the social influence, especially from family, friends, children or even social communities, drives the purchasing intention (Basu, 2015; Conci et al, 2009; Dhar, 2017; East et al, 2014) by generating awareness in the first place, reinforced by subsequent positive word of mouth (Lian & Yen, 2014; Roy et al, 2017). For instance, influence of peers and superiors can have huge impact on the adoption of social networking in the modern societies (Peng & Mu, 2011; Venkatesh & Brown, 2001).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Indian retail customers are price-sensitive by nature (Basu, 2015; Basu, Guin & Sengupta, 2014). In such conditions, the consumers’ WOM intention gets affected by market-level stimuli (Cheung & Thadani, 2012), such as price perception and incentive (Chu & Li, 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Laaksonen (1993) conducted a study on retail format choice decision and found that the demographic characteristics are also the key variables of store choice with regard to a particular format. Customers’ familiarities with the store enable them to purchase more with less perceived risk (Basu, 2015). Shoppers’ personalities, values, lifestyle and their demographic characteristics are the crucial determinants while choosing a particular store (Dodge & Summer, 1969).…”
Section: Literature Reviewmentioning
confidence: 99%